A question of access: metaphors of the field. Issue 1 (2nd January 2020) - Matthiesen, Noomi
ABSTRACT: This article takes a closer look at the issue of access by describing the author's process of access during an ethnographic study on the home–school collaboration between Somali diaspora mothers and teachers in Danish public schools. The article is structured around metaphors of the field and unfolds as a progressive narrative of these metaphors; field as landscape, field as labyrinth, field as marketplace and field as coming to be. It is argued that the field is not a place one can get into but rather a social world comprised of people living their lives entangled with one another. The process of negotiations of access is considered as much a part of developing an understanding of the social world as more formalised research practices such as participant observations and interviewing. Furthermore, our understanding is created through concrete participation as well as our exclusion from participation.